PERSEPSI KONSUMEN TERHADAP FITUR AUGMENTED REALITY SHOPEE DAN DAMPAKNYA TERHADAP KEPUASAN SERTA NIAT PEMBELIAN - Febryan, Putra Hikmah; Loka, Nalendra Pradipta; Indonesia, Haikal Lentera; Aulia, Virdha Rahma (CV. Denasya Smart Publisher, 2025)
The development of Augmented Reality (AR) technology in the e-commerce sector offers new opportunities to enhance online shopping experiences through immersive and interactive features. This study aims to analyze the influence of AR characteristics—interactivity, vividness, novelty, and informativeness—on consumer perceptions (perceived enjoyment, perceived usefulness, and hedonic value), and how these perceptions affect attitudes, satisfaction, and purchase intention on the Shopee platform. A quantitative approach was employed, with data collected from 100 active Shopee users who have experienced using AR features. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that most AR characteristics significantly affect consumer perception. Furthermore, perceived enjoyment, usefulness, and hedonic value were found to influence user attitudes and satisfaction, ultimately increasing purchase intention. This study contributes theoretically to the understanding of AR integration in consumer behavior within e-commerce, and provides practical implications for businesses in designing immersive technology-based marketing strategies.